QUALITATIVE STUDY: MOTHER'S EXPERIENCES IN SELF-CARE DURING PREGNANCY, AND PUBLIC PARTY OF THE SASAMBO TRIBE - Cahyaningtyas, Dwi Kartika (Jurnal Kesehatan Abdurrahman, 2025)
Indonesian society consists of various ethnic groups with different cultural backgrounds, which can affect the behavior of community life including health behavior. There are still many cultural practices that negatively affect people's health behavior, so they are at greater risk of infection. Cultural and social factors influence the high maternal and infant mortality rate. the purpose of this study was to determine how mothers experience self-care during pregnancy, and postpartum in the Sasambo tribe. This research method uses a type of qualitative research with a phenomenological approach, the research design used is Explonatory. Semi-structured interview guide. The sampling technique used is purposeful sampling. The results of this study are described and categorized into 4 major themes, namely maternal health knowledge, the risk of using culture in maternal self-care, the practice of pregnancy care efforts, the practice of postpartum care efforts. The role of parents and husbands was quite influential in the mother's choice of self-care during pregnancy and postpartum. Sasambo cultural traditions such as drinking herbal medicine, abstinence from certain foods, abstinence from activities, massage therapy, recommendations that must be followed, and the existence of rituals during pregnancy have been hereditary applied to every pregnant woman until postpartum in the Sasambo tribe.